Educational Program for Early Childhood Teachers to Enhance Awareness of Child Growth and Development Detection - Adela Kharima Diyenti; Angraini Daboti; Abdul Halif; Fitri Fitri; Putri Arafah (Journal of Comunity Service in Early Childhood Education, 2025)
Background: Awareness of early childhood teachers regarding the detection of child growth and development is essential to support optimal child development and early intervention. However, field conditions indicate that many teachers still have limited understanding and skills in identifying growth and developmental indicators in children. Aims: This program aims to enhance early childhood teachers’ awareness and competence in detecting child growth and development through an educational program. Methods: This program employed a Service Learning approach, integrating educational sessions with practical activities and reflection. The implementation was conducted in three stages: preparation, implementation, and evaluation. The program involved early childhood teachers as participants. Activities included educational sessions, guided practice, and evaluation through pre-test and post-test, as well as observation of participants’ engagement. Data were analyzed descriptively to assess changes in participants’ understanding. Results: The results indicate an improvement in teachers’ awareness and understanding of child growth and development detection. Participants demonstrated better ability to identify developmental indicators and increased readiness to apply detection practices in their institutions. The pre-test and post-test results showed a consistent increase, indicating the effectiveness of the educational intervention. Conclusion: The educational program effectively enhances early childhood teachers’ awareness of child growth and development detection. The integration of education and practical activities provides meaningful learning experiences and supports the improvement of teachers’ competence in early detection practices.Awareness